2020
DOI: 10.3892/etm.2020.8458
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone suppresses the immunostimulatory effects of 27‑hydroxycholesterol

Abstract: In cholesterol-fed rabbits, site-specific targeting of prednisolone nanoparticles results in significantly reduced neo-intimal inflammation with a decreased infiltration of monocytes/macrophages. To understand the molecular mechanisms underlying this, the current study investigated whether prednisolone affects the immune attributes of 27-hydroxycholesterol (27OHChol), the major oxidized cholesterol molecule in circulation and tissue, in human (THP-1) monocyte/macrophage cells. THP-1 cells were exposed to 27OHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…It has also been reported that it damages ZO-1, a protein in the tight junction of blood vessels, causing blood leakage from blood vessels, tissue leakage from tissues, and vision loss due to leakage of ocular fluid ( 46 ). Together with previous findings, our results suggest that glucocorticoids may be beneficial in the treatment of inflammatory and autoimmune diseases that occur in the setting of hypercholesterolemia, such as atherosclerosis, due to their potent anti-inflammatory and immunosuppressive effects ( 47 48 49 ). Taken together, these results show that glucocorticoids, a widely used clinical drug, effectively suppress the inflammatory immune response triggered by increased oxysterols in the body.…”
Section: Discussionsupporting
confidence: 86%
“…It has also been reported that it damages ZO-1, a protein in the tight junction of blood vessels, causing blood leakage from blood vessels, tissue leakage from tissues, and vision loss due to leakage of ocular fluid ( 46 ). Together with previous findings, our results suggest that glucocorticoids may be beneficial in the treatment of inflammatory and autoimmune diseases that occur in the setting of hypercholesterolemia, such as atherosclerosis, due to their potent anti-inflammatory and immunosuppressive effects ( 47 48 49 ). Taken together, these results show that glucocorticoids, a widely used clinical drug, effectively suppress the inflammatory immune response triggered by increased oxysterols in the body.…”
Section: Discussionsupporting
confidence: 86%
“…Our results revealed that normal HSPC indeed exhibits an increased expression of ERα in response to 27HC treatment. We have previously explored the molecular pathways affected by 27HC treatment in THP1 cells [ 47 ]. To assess whether 27HC affects HSPC, we exposed HSPCs in BM cells to 6.2 µM 27HC for 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, drugs that regulate the activities of 27OHChol are likely to have antiinflammatory or immunosuppressive effects. Accordingly, immunosuppressive drugs, such as dexamethasone, prednisolone, and cyclosporine A, have been reported to inhibit the 27OHChol-induced activation of monocytes (Kim et al, 2017;Lee et al, 2019;Kim et al, 2020). In addition, diclofenac, a non-steroidal anti-inflammatory drug, and reblastatin, which exhibits anticancer effects, and 4-Omethylalpinumisoflavone, which displays anti-inflammatory effects against LPS, suppress 27OHChol-induced monocytic cell activation (Son et al, 2017;Lee et al, 2019;Choi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%